A comparative randomized clinical trial evaluating the efficacy and safety of tacrolimus versus hydrocortisone as a topical treatment of atopic dermatitis in children - Mohamed, Amal A.; El Borolossy, Radwa; Salah, Eman M.; Hussein, Maha S.; Muharram, Nashwa M.; Elsalawy, Naglaa; Khalil, Mona G.; Mahmoud, Maha O.; El-Amir, Reham Y.; Elsanhory, Heba M. A.; Ahmed, Nourelhuda; Adaroas, Ahmed S.; et al. (Frontiers in Pharmacology, 2023)
Background: Atopic dermatitis (AD) aetiology is not exactly identified, but it is characterized by pruritic skin reactions with elevation in the levels of inflammatory markers. Despite the fact that Corticosteroids are the mainstay therapy in the management of AD, they have many local and systemic adverse effects. Objective: The aim of this study is to evaluate the efficacy and safety of topical tacrolimus ointment in comparison to topical hydrocortisone cream in the management of the AD of children diagnosed with AD. Patients and Methods: This study was conducted on 200 children with AD. They were simply randomized into two groups, the tacrolimus group treated with 0.03% topical tacrolimus ointment and the hydrocortisone group treated with 1% hydrocortisone cream twice daily during the 3 weeks study period. Results: At the end of the study, both the tacrolimus and hydrocortisone groups showed a significant decline in the mean serum level of IL-10, IL-17, and IL-23 (p < 0.05) when compared to their baseline levels. However, the tacrolimus group showed a more significant decrease (p < 0.05) in the mean serum level of IL-10, IL-17, and IL-23 as compared to the hydrocortisone group [Mean differences = 1.600, 95% CI: 0.9858–2.214; 1.300, 95% CI: 1.086–1.514 and 4.200, 95% CI: 3.321–5.079]. Moreover, the median mEASI decreased similarly from 32 to 21 in the tacrolimus group and from 30 to 22 in the hydrocortisone group (p > 0.05) [Median difference = −2.000, 95% CI: −2.651 to −1.349; Median difference = 1.000, 95% CI: 0.3489–1.651]. Mild to moderate transient stinging and erythema were the main adverse effects that showed higher incidence in the tacrolimus group than in the hydrocortisone group (p < 0.05). In most cases, they resolved within 3–4 days. Besides, tacrolimus ointment did not cause skin atrophy as compared to the hydrocortisone group (p < 0.05). Conclusion: Tacrolimus ointment is more beneficial than hydrocortisone cream in managing AD in children in terms of lowering the inflammatory markers, however, there is no difference on the dermatitis severity scale. Moreover, tacrolimus is safer with a better side effect profile compared to hydrocortisone. Trial Registration: The trial is registered at ClinicalTrials.gov (CT.gov identifier: NCT05324618)